Deciphering the black-box of monetary policy transmission in South Asia - Mohammad, Khalil Ullah; Khan, Mohsin Raza (Economic Journal of Emerging Markets, 2024)
Purpose ─ This study aims to identify the role of the bank capital channel by investigating how monetary policy affects bank lending through its influence on bank equity capital in the transmission of monetary policy.Method ─ The panel vector autoregression (pVAR) is employed to investigate the complex relationship between monetary policy shocks, bank capital, and lending behavior. Results ─ The main findings are as follows: 1) The study finds evidence of both the bank lending and bank capital channels in South Asia. The analysis reveals a Granger causality between changes in bank capital position and policy rate adjustments, indicating a dynamic interplay between these variables. 2) The findings suggest that although the direct effects of capital position changes on bank lending appear negligible, a nuanced examination uncovers the moderating influence of capital position changes on the impact of policy rate fluctuations on lending behavior. 3) The study suggests that healthier banking systems weaken the bank lending channel in South Asia.Implication ─ The research sheds light on the mechanism involved in the interplay between monetary policy, bank capital, and lending, providing valuable insights for policymakers and future research directions.Originality ― This study seeks to fill a gap in the existing literature that offers limited evidence regarding the bank capital channel of monetary policy transmission mechanism, especially within the context of the South Asian region.